Pola Peresepan Obat Psikotropika Di Apotek Karangrejo Kota Semarang - Paulina Maya Octasari; Devita Wityaninda (Prodi D3 Farmasi Politeknik Katolik Mangunwijaya, 2023)
Psychotropics can lead to dependence if misused or used without control and supervision. Psychotropic drugs can only be given using a prescription in healt facilities such as pharmacies, clinics or hospitals. One way to control and supervise psychotropic drugs is to plan. This study aims to determine the pattern of prescribing psychotropic drugs at the Karangrejo’s Pharmacy, Semarang City. This research is a type of descriptive observational research. The design of this research is a Cross-Sectional Study. The data collected is retrospective, in the period October - December 2022. The data source is a psychotropic drug prescription sheet at the Karangrejo Pharmacy, Semarang City. The data collected included date of prescription, prescription number, age, gender, origin of prescription, psychotropic drug used and dosage. The data were analyzed qualitatively, grouping data based on patient and prescription characteristics. Patient characteristics include the patient's age and gender while prescription characteristics include the origin of the prescription, and the psychotropic drugs used include the name of the drug, drug class, amount of drug therapy and drug combinations. Quantitative analysis is by calculating the percentage of data that has been processed. From this study, the data obtained were 106 patients who received psychotropic drugs at the Karangrejo Pharmacy, Semarang City. From the results of this study, it was obtained that the most age group was 56-65 years (34.91%) with the most gender, namely women (65.09%), the origin of the prescription that prescribed the most psychotropics was prescription from external doctors (50.94%) with the highest speciality of prescribing doctors, namely specialist doctors (82.07%), the most widely used type of psychotropic drug, namely Chlordiazepoxide (50.73%), the highest number of drug therapies, namely single drug therapy (76.42%), the highest drug combinations namely Chlordiazepoxide 5mg and diazepam 2mg (56%), and the most common class of therapy was antispasmodics (50.72%).